Shaping the New Financial System - Moretti, Marina; Kodres, Laura; Narain, Aditya; Pazarbasioglu, Ceyla (Washington, D.C. : International Monetary Fund, 2010)
Three years after the onset of the global financial crisis, much has been done to reform the global financial system, but there is much left to accomplish. The regulatory reform agenda agreed by G-20 leaders in 2009 has elevated the discussions to the highest policy level and kept international attention focused on establishing a globally consistent set of rules. Comprehensive reform, once agreed and implemented in full, will have far-reaching implications for the global financial system and the performance of the world economy. In designing the reforms, it is imperative that policymakers keep their focus on the overarching objective of creating a financial system that provides a solid foundation for strong and sustainable economic growth. This paper argues that the current reforms are moving in the right direction, but many policy choices lie ahead-nationally and internationally?which are both urgent and challenging. Policies need to address not only the risks posed by individual banks but also, importantly, those posed by nonbanks and the system as a whole. The recent proposals of the Basel Committee on Banking Supervision (BCBS) represent a substantial improvement in the quality and quantity of bank capital, but these apply only to a subset of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet